Mind on statistics - Utts, Jessica M.; Heckard, Robert F.; Torri, Lisa. ([S.l.] : Thomson-Brooks/Cole, 2003)
Emphasizing the conceptual development of statistical ideas, MIND ON STATISTICS actively engages students and explains topics in the context of excellent examples and case studies. This text balances the spirit of statistical literacy with statistical methodology taught in the introductory statistics course. Jessica Utts and Robert Heckard built the book on two learning premises: (1) New material is much easier to learn and remember if it is related to something interesting or previously known; (2) New material is easier to learn if you actively ask questions and answer them for yourself. More than any other text available, MIND ON STATISTICS motivates students to develop their statistical intuition by focusing on analyzing data and interpreting results as opposed to focusing on mathematical formulation. The new edition of this exciting text, enhanced with new material and features, appeals to a wide array of students and instructors alike.